A multi-class deep learning model for early lung cancer and chronic kidney disease detection using computed tomography images - Bhattacharjee, Ananya; Rabea, Sameh; Bhattacharjee, Abhishek; Elkaeed, Eslam B.; Murugan, R.; Selim, Heba Mohammed Refat M.; Sahu, Ram Kumar; Shazly, Gamal A.; Salem Bekhit, Mounir M. (Frontiers in Oncology, 2023)
Lung cancer is a fatal disease caused by an abnormal proliferation of cells in the lungs. Similarly, chronic kidney disorders affect people worldwide and can lead to renal failure and impaired kidney function. Cyst development, kidney stones and tumors are frequent diseases impairing kidney function. Since these conditions are generally asymptomatic, early and accurate identification of lung cancer and renal conditions is necessary to prevent serious complications. Artificial Intelligence plays a vital role in the early detection of lethal diseases. In this paper, we proposed a modified Xception deep neural network-based computer-aided diagnosis model, consisting of transfer learning based imagenet weights of Xception model and a fine-tuned network for automatic lung and kidney computed tomography multi-class image classification. The proposed model obtained 99.39% accuracy, 99.33% precision, 98% recall and 98.67% F1-score for lung cancer multi-class classification. Whereas, it attained 100% accuracy, F1 score, recall and precision for kidney disease multi-class classification. Also, the proposed modified Xception model outperformed the original Xception model and the existing methods. Hence, it can serve as a support tool to the radiologists and nephrologists for early detection of lung cancer and chronic kidney disease, respectively.